Preparation and properties of ZrO2 and TiO2 films and their nanolaminates by atomic layer deposition. (July 2015) - Chen, Wen; Ren, Wei; Zhang, Yijun; Liu, Ming; Ye, Zuo-Guang
Abstract: Nanolayers of ZrO2 and TiO2 and their nanolaminates were grown on silicon wafer by an atomic layer deposition process. Precursors of tetrakis (dimethylamido) zirconium and tetrakis (dimethylamido) titanium were used to deposit ZrO2 and TiO2 films at different temperatures, respectively. The XRD results show that ZrO2 films began to crystallize at the deposition temperature of 300 °C, and the cubic phase was first formed when the thickness of the film reached 16.5 nm, and then monoclinic phase appeared in the film when the thickness further increased. The as-deposited TiO2 films exhibited anatase phase at the deposition temperature range of 50–300 °C. AFM morphologies indicate that both ZrO2 and TiO2 films were uniform and smooth. Nanolaminates of ZrO2 and TiO2 were obtained by deposition of ZrO2 and TiO2 layers at 300 °C alternatively with precise layer thickness control. The results show that the nanolaminates exhibited a giant dielectric constant of 850 at low frequency which was much higher than the individual dielectric constants of ZrO2 and TiO2 . The nanolaminates of ZrO2 and TiO2 with the giant dielectric constant have potential applications for high- k dielectric materials.